The impact of high-tech industrial agglomeration on China’s green innovation efficiency: A spatial econometric analysis - Liu, Shucheng; Wu, Peijin (Frontiers in Environmental Science, 2023)
Eco-efficiency is an important factor in assessing the quality of development, and high-tech industries are crucial for countries to forge green innovation paths. However, few studies have examined whether and how high-tech industrial agglomeration affects green innovation efficiency. To fill this gap, we measure the degree of high-tech industrial agglomeration and the level of specialized and diversified agglomeration using the location entropy index and agglomeration factor, and calculate green innovation efficiency using the super-SBM model with undesirable outputs. Based on Chinese provincial panel data from 2006 to 2020, a dynamic spatial Durbin model was constructed to explore the impact of high-tech industrial agglomeration and different agglomeration patterns on green innovation efficiency. Our study found that high-tech industrial agglomeration is a significant contributor to green innovation efficiency. There is an inverted U-shaped relationship between specialized agglomeration and green innovation efficiency, and diversified agglomeration contributes to green innovation efficiency. Given the regionally uneven nature of China’s economic development, there is some variation in the impact effects within different economic regions. We demonstrated the leading role of scientific high-tech industrial agglomeration patterns and appropriate levels of agglomeration in green innovation, providing theoretical guidance for the formulation of China’s high-quality development policies.